2013
DOI: 10.1089/dna.2012.1889
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of Endoplasmic Reticulum Quality Control and ER-Associated Degradation Factors

Abstract: Recent studies are delineating a detailed picture of the architecture and function of the endoplasmic reticulum (ER) and the early secretory pathway, showing the existence of dynamic compartmentalization of ER quality control and ER-associated degradation (ERAD) factors. The compartmentalization is regulated by ER protein load and in turn regulates protein processing and cell fate. This compartmentalization is intimately linked to the protein quality control processes, protein disposal through ERAD, the unfold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 67 publications
0
27
0
1
Order By: Relevance
“…This property, together with the enzymatic action of UDPGlc:glycoprotein glucosyltransferase and glucosidases I and II leads to a cyclic interaction of folding substrates with calnexin until proper folding is reached or ERAD is triggered. Our new data now indicate that calnexin itself undergoes a palmitoylationdependent cycle within the ER and shuttles back and forth from regulating Ca 2+ signaling at or close to the MAM and mediating protein folding and quality control at or close to the rough ER, including the targeting of unfolded or misfolded proteins to the ERQC (Leitman et al, 2013). Interestingly, these results could help explain the anti-stress function of 2-bromopalmitate (2BP) treatment, which attenuates the induction of ER stress transcription factors and the progression of apoptosis (Baldwin et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…This property, together with the enzymatic action of UDPGlc:glycoprotein glucosyltransferase and glucosidases I and II leads to a cyclic interaction of folding substrates with calnexin until proper folding is reached or ERAD is triggered. Our new data now indicate that calnexin itself undergoes a palmitoylationdependent cycle within the ER and shuttles back and forth from regulating Ca 2+ signaling at or close to the MAM and mediating protein folding and quality control at or close to the rough ER, including the targeting of unfolded or misfolded proteins to the ERQC (Leitman et al, 2013). Interestingly, these results could help explain the anti-stress function of 2-bromopalmitate (2BP) treatment, which attenuates the induction of ER stress transcription factors and the progression of apoptosis (Baldwin et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Our data also suggest that these aggregates may reflect mutant s-1R clustering at ER subcompartments where BiP is excluded. One such specialization is the ER quality control compartment (ERQC), which forms during ER stress (Kamhi-Nesher et al, 2001;Frenkel et al, 2004;Kondratyev et al, 2007;Leitman et al, 2013). Indeed, pharmacologic induction of ER stress results in the clustering of the unfolded protein response proteins (UPR) protein kinase RNA-like ER kinase (Kondratyev et al, 2007) and inositol-requiring protein 1 (IRE1) at ERQCs (Kimata et al, 2007;Aragon et al, 2009;Li et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on ER-derived inclusion-like structures that are formed after expression of mutated ER proteins in yeast or mammalian cells [55,58-60]. An ER-derived structure termed ERPO (ER protective organelle) has been identified as a protective ER compartment in cells expressing the serpin α1-antitrypsin with an E342K mutation, associated with liver disease in children [58].…”
Section: Discussionmentioning
confidence: 99%